一种环控热管理系统简化建模方法 (2022)
本申请属于飞机能量管理技术领域，涉及一种环控热管理系统简化建模方法。该方法包括：将综合环控及热管理系统划分为空气循环制冷子系统、蒸发循环制冷子系统、高温液冷循环子系统、低温液冷循环子系统以及燃油循环子系统，各子系统间通过换热器进行耦合；在各子系统间的换热器处断开，从而对各子系统分别进行建模，其中，所述空气循环制冷子系统与所述蒸发循环制冷子系统采用响应面代理模型进行简化；将各子系统模型间的换热器进行耦合连接，搭建综合环控及热管理系统模型；输入飞行工况，进行仿真计算。本申请以子系统间换热器进行耦合，形成大系统的简化模型，有效提升了计算效率，同时保证了计算结果的准确性。 The invention belongs to the technical field of aircraft energy management, and relates to a simplified modeling method for an environment control and thermal management system. The method comprises the steps that a comprehensive environmental control and thermal management system is divided into an air circulation refrigeration subsystem, an evaporation circulation refrigeration subsystem, a high-temperature liquid cooling circulation subsystem, a low-temperature liquid cooling circulation subsystem and a fuel circulation subsystem, and all the subsystems are coupled through heat exchangers; the positions of the heat exchangers between the subsystems are disconnected, so that modeling is conducted on the subsystems, and the air